Nursing outcomes in wound care management: A mixed method study. Issue 4 (7th December 2022) - Lommi, Marzia; Raffaele, Barbara; Tolentino Diaz, Maria Ymelda; Montini, Graziella; Puleio, Cinzia; Porcelli, Barbara
Abstract: Aim: The aim of the study was to analyse the management of chronic wound outcomes and the experience of patients with chronic ulcers. Design: Explanatory mixed method. Methods: This study consisted in a sequential explanatory mixed method with a quantitative and a qualitative phase. In the first phase, quantitative data were collected during a longitudinal study, in a convenience sample of 44 patients presenting at a nursing outpatients' clinic. Linear regression was conducted to evaluate the associations between variables. In phase two, 14 patients from the initial sample were interviewed, and the data were analysed using Giorgi's descriptive phenomenological method. Results: The participants, mostly males, in conditions of comorbidity and polypharmacotherapy, were mainly affected by venous leg ulcers. An association between the quality of life of patients (both physical and mental) and some socio‐demographic and clinical factors has been confirmed. I Variance analysis showed a significant wound improvement across all the measurement times. The themes identified through the qualitative analysis were: "Cared by self, " "Cared by Healthcare Providers" and "Quality of life".